URBAN COHESION AND MOBILITY IN THE CITY OF BATNA - Chebana Hakim (International Journal of Innovative Technologies in Social Science, 2025)
This research paper addresses the phenomenon of urban growth in the city of Batna, by defining the related terminology, reviewing the key stages the city has gone through, and identifying the causes of the phenomenon along with the various factors influencing the population and urban areas. It also examines the effects of urbanization and its impacts on mobility, the urban and environmental contexts, as well as the surrounding environment. The study concludes by recognizing the serious risks that this phenomenon poses both to the city and its inhabitants. It emphasizes the need to provide all resources and knowledge necessary to mitigate and manage this growth, while meeting today’s needs and preserving the demands of future generations. It also provides comprehensive strategic plans for well-designed urban planning, addressing multiple aspects and reducing unregulated urban sprawl to balance rural and urban areas while preserving valuable, non-renewable natural resources.